(untitled) (Research, Society and Development, 2022)
The objective of the study was to understand what are the main themes of research related to music teaching in high school. To this end, a qualitative research was carried out to analyze the content of 16 articles retrieved in Revista da Abem and in the repositories of Scielo and Capes. The theoretical basis was based on principles referring to the teaching of music in high school. The findings showed that the main themes of academic research on music teaching in high school are: high school students’ musical preference; training of high school music teachers and pedagogical proposals; music teaching in high school; legislation on Music Education in High School; and relationships, conceptions and musical culture of high school students.